Ethical considerations to carry out social research in rural communities of the municipality of Amealco de Bonfil - Velázquez Hernández, Jorge Arturo; Alonso Chombo, Rosalía; Romero Zepeda, Jorge Adán (Advances in Social Sciences Research Journal, 2021)
The objective of this research is to collect culturally timely information to develop research protocols in the university context for the indigenous population. Theoretically, it starts from the assertion that in social disciplines informed consent is essential to carry out ethical scientific activity; and therefore, institutional mechanisms must be developed to safeguard this informed consent. As a strategy of approaching the community, a training course for entrepreneurship was given, where eight surveys were carried out. In field work, there is an enthusiasm of the population for the development of social scientific activities in indigenous communities; especially if community members are involved in all phases of the investigation. From the above, it is concluded that an institutional mechanism for the academy to act ethically with the indigenous population is that the members of the community participate in all phases of the investigation.